Documents regarding the «desfillamiento» (disinheritance) in Aragón in the 15th and 17th Century - Gómez de Valenzuela, Manuel (Revista de derecho aragonés, 2018)
This is a study about «desfillamiento» (disinheritance) in Aragonese Law. We must point out that this responds to an extreme and exceptional situation. The causes and effects of «desfillamiento» in Aragonese Law are analysed, by means of the documents that have been found. The documents attached as an annex are described and explained.